Religion in Personal Space: Religious Practices and Dynamics of Family Harmony in Padang City - Maihasni Maihasni; Nini Anggraini; Fachrina Fachrina; Faiz Badridduja; Indeska Putra (LPPM Universitas PGRI Sumatera Barat, 2026)
This study discusses religious practices in harmonious families by focusing on religious practices carried out by harmonious families in Padang City. This study aims to analyze religious practices carried out by harmonious families in Padang City and factors that support family harmony through religious practices. The theory used in this study is the structuring of Giddens. This research uses a qualitative approach with a descriptive-interpretive method. The selection of informants was carried out by purposive sampling, and data was collected through in-depth interviews, and participatory observation. The results of this study found that religious practices carried out by harmonious families in Padang City are divided into two categories, namely: compulsory worship and sunnah worship with their implementation carried out individually and collectively. Factors that support family harmony through religious practices are: religious obedience and faith, sincere affection and sacrifice, openness and effective communication, patience and tawakal.